Reduction to homozygosity involving p53 in esophageal cancers demonstrated by the polymerase chain reaction. - Stephen J. Meltzer; Jie Yin; Ying Huang; T K McDaniel; Carnell Newkirk; Oscar A. Iseri; Bert Vogelstein; James H. Resau (1991)
Loss of heterozygosity affecting chromosome 17p has been detected at high frequencies in a variety of human tumors, including cancers of the colon, breast, lung, and brain. One presumed target of these losses is p53, a tumor suppressor gene located on 17p. To our knowledge, loss of heterozygosity has not yet been reported at any locus, including p53, in human esophageal cancer. Moreover, current methods of detecting loss of heterozygosity depend on the availability of large amounts of high molecular weight DNA, making the study of small biopsy specimens or paraffin-embedded tissues problematic. We examined 52 primary human esophageal neoplasms for loss of heterozygosity affecting the p53 gene by using the polymerase chain reaction. Loss of one allele was detected in 52% of informative cases and was more common in squamous carcinomas than in adenocarcinomas. Southern blot analysis was used to confirm polymerase chain reaction-derived data. The identification of allelic loss in approximately half of the tumors analyzed supports the hypothesis that inactivation of p53 is involved in the pathogenesis of esophageal cancer.